The role of electronic publishing in providing information services - Douniazed, Souyah; Bouguerne, Toufik; Abassi, Krima (The International tax journal, 2025)
The Internet is one of the most significant achievements of modern technological advancements, enabling individuals to access any information or service they need from anywhere in the world. The acquisition of knowledge has evolved, now relying on electronic technologies that facilitate rapid access to information, minimizing both time and effort. This transformation has eliminated the need for researchers to physically travel in search of information, as various digital tools—such as e-books and electronic journals—have revolutionized teaching and academic learning through electronic publishing. The significance of electronic publishing lies in its role as one of the most advanced information technologies in the era of the digital revolution. It enables seamless access to diverse information in a virtual space, allowing users to retrieve content with the mere click of a button. Moreover, electronic publishing has contributed to saving time and effort while reducing costs related to travel, printing, and other logistical aspects. This digital shift fosters interactivity and optimizes space utilization by eliminating the need for traditional printed documents, replacing them with electronic devices (such as computers) that store a wide range of digital materials, which can be easily retrieved at any time.